Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/3109561
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Influence of China’s Carbon Emissions Trading Scheme on Green Innovation of Enterprises

Abstract: China’s economic growth has entered “new normal,” and the task of reducing carbon emissions has become more onerous. Hence, this study aimed to explore whether China’s carbon emissions trading pilot policy stimulated corporate green innovation capabilities. The data pertained to the green patent data of the listed companies in Shanghai and Shenzhen stock exchanges during 2008–2018. Using a difference-in-difference-in-differences (DDD) method, the study took advantage of the variations across regions, across en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Liu, Baoliu [9] 2021 In pilot regions, carbon emissions equity trading policies can improve total factor productivity in the green economy. Qi, Yawei [11] 2022…”
Section: Dong Xuan Et Al [3] 2020mentioning
confidence: 99%
“…Liu, Baoliu [9] 2021 In pilot regions, carbon emissions equity trading policies can improve total factor productivity in the green economy. Qi, Yawei [11] 2022…”
Section: Dong Xuan Et Al [3] 2020mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%